Flame-retardant fire early-warning bacterial cellulose aerogel fiber and preparation method thereof

By constructing a phytic acid-doped polypyrrole flame retardant conductive layer and ZnO@MXene fire warning layer on the surface of bacterial cellulose aerogel fiber, the problems of flammability and poor mechanical properties of bacterial cellulose aerogel fiber are solved, and the flame retardant and fire warning performance are significantly improved.

CN119736793AActive Publication Date: 2025-04-01JIANGNAN UNIV

Patent Information

Application Number
CN202411933159.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Bacterial cellulose aerogel fiber is flammable, has low skeleton strength, and has poor mechanical properties, which limits its large-scale application.

Method used

By preparing bacterial cellulose hydrogel fibers, and phytic acid-doped polypyrrole flame retardant conductive layer is constructed on its surface by in-situ chemical oxidation polymerization. Finally, a fire warning layer of ZnO@MXene nanohybrid material is constructed outside the flame retardant conductive layer to obtain flame retardant fire warning bacterial cellulose aerogel fiber.

Benefits of technology

The flame retardant performance and fire warning performance of bacterial cellulose aerogel fiber are significantly improved, the heat release rate and total heat release amount are reduced, and its ability to form a carbonized layer at high temperatures is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736793A_ABST
    Figure CN119736793A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of flame-retardant fire early-warning bacterial cellulose aerogel fibers, and belongs to the technical field of materials. According to the preparation method, bacterial cellulose is taken as a core raw material, then a phytic acid-polypyrrole conductive network is constructed in the fiber through a solvent replacement effect, and a ZnO-MXene sensing material with high flame sensitivity is further covered on the surface, so that the flame-retardant bacterial cellulose aerogel fiber with excellent flame retardance and high flame sensitivity is prepared. The preparation method is simple, convenient and efficient, resource recycling is effectively promoted, and the prepared flame-retardant fire early-warning bacterial cellulose aerogel fiber has wide application prospects in the fields of vehicle interiors, clothes and furniture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flame-retardant fire warning bacterial cellulose aerogel fiber and a preparation method thereof, belonging to the technical field of materials. Background Art

[0002] Aerogel fiber is a highly porous solid material with low density and extremely low thermal conductivity. Its unique continuous network pore structure gives it excellent thermal insulation and heat preservation properties, making it an ideal candidate material for the preparation of advanced thermal insulation textiles. The application of such materials has significantly promoted the development of thermal insulation textiles towards lightweight and high-efficiency thermal insulation performance. The uniqueness of aerogel fiber lies in its successful integration of the lightweight and porous advantages of aerogel materials with the inherent flexibility and slenderness of fiber materials, thus giving it good weaving potential. By directly weaving aerogel fibers or blending them with other fiber materials, the inherent properties of various materials can be effectively integrated and optimized, and the performance can be complemented and enhanced, opening up a new path for the innovative design and manufacture of thermal insulation textiles. Among them, bacterial cellulose-based aerogel fibers prepared using bacterial cellulose as raw materials not only have the inherent advantages of aerogel fibers, but also show good biocompatibility and degradability. However, they are flammable, have low skeleton strength, and poor mechanical properties. These shortcomings limit the large-scale application of bacterial cellulose aerogel fibers. Therefore, developing a new method to improve the strength, flame retardancy and flame warning performance of bacterial cellulose aerogel fibers is of great significance to further expand the application scope of bacterial cellulose aerogel fibers.

[0003] At present, the prior art patent CN 118390291 A discloses a MoS 2 @MXene-based gas-sensitive flame-retardant coating and its application in textiles, but it is aimed at ordinary fabrics rather than bacterial cellulose-based aerogel fibers, and the disclosed solution does not produce excellent results when applied to bacterial cellulose-based aerogel fibers. Summary of the invention

[0004] Technical issues

[0005] Bacterial cellulose aerogel fiber is a material with the advantages of softness, warmth, high biocompatibility and degradability. However, it is flammable, has low skeleton strength and poor mechanical properties, and therefore cannot be used on a large scale. Therefore, it is necessary to develop a new method for preparing bacterial cellulose aerogel fiber and give it a flame retardant effect.

[0006] Technical Solution

[0007] To solve the above problems, the present invention prepares bacterial cellulose hydrogel fibers, then constructs a phytic acid-doped polypyrrole flame-retardant conductive layer on the surface of the cellulose hydrogel fibers by in-situ chemical oxidation polymerization, and finally constructs a fire warning layer outside the flame retardant conductive layer to obtain a flame retardant and fire warning bacterial cellulose aerogel fiber.

[0008] The present invention provides a method for preparing flame-retardant fire warning bacterial cellulose aerogel fibers, the preparation method comprising the following steps:

[0009] (1) Preparation of bacterial cellulose hydrogel fibers: placing bacterial cellulose powder in an organic solvent and stirring to prepare a spinning solution, and wet spinning the spinning solution to obtain bacterial cellulose hydrogel fibers;

[0010] (2) Preparation of PA@PPy flame retardant conductive layer: phytic acid, pyrrole and low molecular weight alcohol are mixed to prepare a mixed solution, and the cellulose hydrogel fiber prepared in step (1) is immersed in the mixed solution, and then an ammonium persulfate solution is added. After standing, the cellulose hydrogel fiber is taken out and washed to obtain a conductive cellulose hydrogel fiber;

[0011] (3) Preparation of fire warning layer: Add ZnO@MXene nano-hybrid material into water and stir to form a dispersion, immerse the conductive cellulose hydrogel fiber obtained in step (2) into the dispersion, then take out the conductive cellulose hydrogel fiber and freeze-dry it to obtain flame-retardant fire warning bacterial cellulose aerogel fiber.

[0012] In one embodiment of the present invention, the organic solvent in step (1) includes one or more of N,N-dimethylacetamide, N-methylpyrrolidone, acetone, dimethyl sulfoxide, toluene, tetrahydrofuran, acetonitrile, cyclohexanone, cyclohexane, and ethyl acetate.

[0013] In one embodiment of the present invention, the stirring in step (1) includes ultrasonic stirring and / or mechanical stirring.

[0014] In one embodiment of the present invention, the stirring time in step (1) is 5 min to 24 h.

[0015] In one embodiment of the present invention, the concentration of bacterial cellulose in the spinning solution in step (1) is 5 to 15 wt%.

[0016] In one embodiment of the present invention, the wet spinning process in step (1) comprises pressing the spinning solution out of the spinneret holes of the spinning device to form a spinning stream, and the spinning stream is coagulated and drawn into nascent fibers in a coagulation bath.

[0017] In one embodiment of the present invention, the wet spinning in step (1) is performed by using a wet spinning device; the inner diameter of the spinning needle is 0.5 to 1 mm, and the extrusion rate is 50 to 100 μL / min.

[0018] In one embodiment of the present invention, the coagulation bath in the wet spinning in step (1) is deionized water.

[0019] In one embodiment of the present invention, the drafting ratio in the wet spinning in step (1) is 1.2 to 2 times.

[0020] In one embodiment of the present invention, the concentration of phytic acid in the mixed solution in step (2) is 0.2-0.3 g / mL.

[0021] Preferably, the concentration of phytic acid in the mixed solution in step (2) is 0.25-0.28 g / mL.

[0022] Specifically, optionally, the concentration of phytic acid in the mixed solution in step (2) is 0.27 g / mL.

[0023] In one embodiment of the present invention, the concentration of pyrrole in the mixed solution in step (2) is 0.1-0.2 g / mL.

[0024] In one embodiment of the present invention, the low molecular weight alcohol in step (2) includes one or more of methanol, ethanol, propanol, and isopropanol.

[0025] In one embodiment of the present invention, the immersion time in step (2) is 1 to 10 minutes.

[0026] In one embodiment of the present invention, the concentration of the ammonium persulfate solution in step (2) is 0.1-0.2 g / mL.

[0027] In one embodiment of the present invention, the mass ratio of phytic acid to ammonium persulfate in step (2) is 1 to 1.5:1.

[0028] In one embodiment of the present invention, the standing time in step (2) is 1 to 10 minutes.

[0029] In one embodiment of the present invention, the cleaning in step (2) is performed using water for 1 to 5 times, followed by drying.

[0030] In one embodiment of the present invention, the preparation method of the ZnO@MXene nanohybrid material in step (3) is:

[0031] Lithium fluoride is added to the hydrochloric acid aqueous solution to react, and then Ti is added 3 AlC2 Continue the reaction, then centrifuge the reaction solution, retain the precipitate and wash it with water until its pH is neutral, then mix the washed precipitate with water and ultrasonicate it, collect the upper suspension and freeze-dry it to obtain MXene powder; weigh the zinc source, sodium hydroxide, and MXene powder, add them to water, stir and then perform a hydrothermal reaction, then wash and dry the obtained reaction product to obtain ZnO@MXene nanohybrid material.

[0032] Furthermore, the concentration of the hydrochloric acid aqueous solution is 5-10M.

[0033] Furthermore, the ratio of the mass of lithium fluoride to the volume of the hydrochloric acid aqueous solution is 1 g:10-30 mL.

[0034] Furthermore, lithium fluoride and Ti 3 AlC 2 The mass ratio is 1 to 1.5:1.

[0035] Furthermore, adding Ti 3 AlC 2 The temperature of the pre-reaction is 20-30°C and the time is 20-60 minutes.

[0036] Furthermore, adding Ti 3 AlC 2 The post-reaction temperature is 30-40°C and the reaction time is 20-24h.

[0037] Furthermore, the zinc source includes one or more of zinc acetate, zinc nitrate and zinc chloride.

[0038] Furthermore, the mass ratio of the zinc source to the sodium hydroxide is 1-3:3-8.

[0039] Furthermore, the mass ratio of the zinc source to the MXene powder is 1-3:1-5.

[0040] Furthermore, the temperature of the hydrothermal reaction is 120-170° C., and the time is 10-20 hours.

[0041] In one embodiment of the present invention, the concentration of the ZnO@MXene nanohybrid material in the dispersion in step (3) is 3 to 10 mg / mL.

[0042] Preferably, the concentration of the ZnO@MXene nanohybrid material in the dispersion in step (3) is 4 to 6 mg / mL.

[0043] Specifically, optionally, the concentration of the ZnO@MXene nanohybrid material in the dispersion in step (3) is 5 mg / mL.

[0044] In one embodiment of the present invention, the soaking time in step (3) is 10 min to 60 min, and the soaking temperature is 15 to 30°C.

[0045] The present invention provides flame-retardant fire warning bacterial cellulose aerogel fibers prepared according to the preparation method.

[0046] The invention provides a flame-retardant fire warning bacterial cellulose aerogel fiber. The flame-retardant fire warning bacterial cellulose aerogel fiber is composed from the inside to the outside of: a fiber layer, a phytic acid-doped polypyrrole flame-retardant conductive layer and a ZnO@MXene nano-hybrid material flame sensing layer.

[0047] Furthermore, the diameter of the fiber layer is 150-250 μm, the diameter of the phytic acid-doped polypyrrole flame-retardant conductive layer is 10-30 μm, and the diameter of the ZnO@MXene nano-hybrid material flame sensing layer is 30-60 nm.

[0048] Furthermore, the fiber layer is prepared by wet spinning a spinning solution prepared from bacterial cellulose powder.

[0049] Furthermore, the phytic acid-doped polypyrrole flame-retardant conductive layer is constructed on the surface of cellulose hydrogel fiber by in-situ chemical oxidation polymerization using phytic acid as a dopant, pyrrole as a monomer, ammonium persulfate as an initiator, and low molecular weight alcohols as a displacement solvent.

[0050] Furthermore, the fire warning layer is composed of ZnO@MXene nano-hybrid materials.

[0051] Furthermore, the preparation method of ZnO@MXene nanohybrid material is: adding lithium fluoride to a hydrochloric acid aqueous solution for reaction, and then adding Ti 3 AlC 2 Continue the reaction, then centrifuge the reaction solution, retain the precipitate and wash it with water until its pH is neutral, then mix the washed precipitate with water and ultrasonicate it, collect the upper suspension and freeze-dry it to obtain MXene powder; weigh the zinc source, sodium hydroxide, and MXene powder, add them to water, stir and then perform a hydrothermal reaction, then wash and dry the obtained reaction product to obtain ZnO@MXene nanohybrid material.

[0052] Furthermore, the concentration of the hydrochloric acid aqueous solution is 5-10M.

[0053] Furthermore, the ratio of the mass of lithium fluoride to the volume of the hydrochloric acid aqueous solution is 1 g:10-30 mL.

[0054] Furthermore, lithium fluoride and Ti 3 AlC 2 The mass ratio is 1 to 1.5:1.

[0055] Furthermore, adding Ti 3 AlC 2 The temperature of the pre-reaction is 20-30°C and the time is 20-60 minutes.

[0056] Furthermore, adding Ti 3 AlC 2 The post-reaction temperature is 30-40°C and the reaction time is 20-24h.

[0057] Furthermore, the zinc source includes one or more of zinc acetate, zinc nitrate and zinc chloride.

[0058] Furthermore, the mass ratio of the zinc source to the sodium hydroxide is 1-3:3-8.

[0059] Furthermore, the mass ratio of the zinc source to the MXene powder is 1-3:1-5.

[0060] Furthermore, the temperature of the hydrothermal reaction is 120-170° C., and the time is 10-20 hours.

[0061] The present invention provides application of the flame-retardant fire warning bacterial cellulose aerogel fiber in the fields of textiles, clothing, furniture or decorations.

[0062] Beneficial Effects

[0063] (1) The present invention adopts an environmentally friendly strategy, using bacterial cellulose as the core raw material, which has a wide range of sources, a green and pollution-free production process, and is environmentally degradable, effectively promoting the concept of green environmental protection and sustainable development. This design shows great significance in protecting the ecological environment and promoting resource recycling.

[0064] (2) Compared with the traditional "impregnation-baking" flame retardant finishing method, the present invention uses a solvent replacement method to infiltrate the phytic acid-doped polypyrrole flame retardant conductive layer into the fiber interior, further improving the flame retardant effect and water washability. The flame retardant fire warning bacterial cellulose aerogel fiber obtained exhibits a synergistic flame retardant system integrating acid source, gas source, and carbon source, which can effectively catalyze the aerogel fiber to form a dense carbonized layer at high temperature, significantly enhancing the flame retardant properties of the aerogel fiber.

[0065] (3) The flame-retardant fire warning bacterial cellulose aerogel fiber prepared by the present invention effectively exerts the gas phase flame retardant effect of phytic acid catalysis and polypyrrole, thereby improving the flame retardancy of the aerogel fiber. The total heat release amount and the peak heat release rate are reduced by 85% and more than 80% respectively compared with ordinary bacterial cellulose aerogel fibers.

[0066] (4) The flame-retardant fire warning bacterial cellulose aerogel fiber prepared by the present invention effectively exerts the synergistic fire warning effect of ZnO and MXene. Within 1.3 seconds of contact with the fire, the flame response intensity reaches 89.3%.

[0067] (5) The method of the present invention is simple, efficient, controllable and repeatable. The aerogel fiber component is green and environmentally friendly. It improves the flame retardant and fire warning properties of bacterial cellulose aerogel fibers, which is conducive to the development of functional aerogel fiber textiles with flame retardant and fire warning functions. The problem of flammability of bacterial cellulose aerogel fibers has been overcome, and it has a wide range of application scenarios in the fields of vehicle interiors, clothing, and furniture. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 This is a flow chart for preparing the flame-retardant fire warning bacterial cellulose aerogel fiber prepared in Example 1;

[0069] Figure 2 This is a digital photo of the flame-retardant fire warning bacterial cellulose aerogel fiber prepared in Example 1;

[0070] Figure 3 This is a Fourier infrared (FTIR) image of the flame-retardant fire warning bacterial cellulose aerogel fiber prepared in Example 1;

[0071] Figure 4 The scanning electron microscope (SEM) images of the flame retardant fire warning bacterial cellulose aerogel fiber and the bacterial cellulose aerogel fiber prepared in Example 1;

[0072] Figure 5 This is a burning digital photo of the flame-retardant fire warning bacterial cellulose aerogel fiber braid prepared in Example 1;

[0073] Figure 6 The thermal weight loss (TG) and thermal weight loss rate (DTG) curves of the flame retardant fire warning bacterial cellulose aerogel fiber and the common bacterial cellulose aerogel fiber prepared in Example 1;

[0074] Figure 7 This is a heat release rate (HRR) diagram of the flame retardant fire warning bacterial cellulose aerogel fiber and the common bacterial cellulose aerogel fiber prepared in Example 1;

[0075] Figure 8 This is a total heat release (THR) diagram of the flame retardant fire warning bacterial cellulose aerogel fiber and the common bacterial cellulose aerogel fiber prepared in Example 1;

[0076] Fig. 9 This is a fire warning image of the flame-retardant fire warning bacterial cellulose aerogel fiber prepared in Example 1;

[0077] Fig.10 This is an infrared thermal imaging image of the flame-retardant fire warning bacterial cellulose aerogel fiber fabric prepared in Example 1 placed on a human palm. DETAILED DESCRIPTION

[0078] Source of raw materials

[0079] Bacterial cellulose powder (BC) was prepared by freeze-drying and then pulverizing the aqueous dispersion purchased from Guilin Qihong Technology; phytic acid, pyrrole, zinc oxide, lithium fluoride, and hydrochloric acid were all purchased from Sinopharm Chemical Reagent Co., Ltd.; Ti 3 AlC 2 All the raw materials were purchased from Jilin Yiyi Technology Co., Ltd. Unless otherwise specified, other raw materials used were common commercial products.

[0080] Test Method

[0081] In the present invention, a Fourier transform infrared instrument is used to measure the molecular bond structure of the flame retardant fire warning bacterial cellulose aerogel fiber.

[0082] In the present invention, a scanning electron microscope is used to observe the surface morphology of bacterial cellulose aerogel fibers and flame retardant fire warning bacterial cellulose aerogel fibers.

[0083] In the present invention, a micro calorimeter is used to measure the heat release rate and total heat release of bacterial cellulose aerogel fibers and flame retardant fire warning bacterial cellulose aerogel fibers; the mass of the test sample is 5-10 mg, the heating rate is set to 1°C / s, and the test temperature range is 100-800°C.

[0084] In the present invention, a thermogravimetric analyzer is used to determine the thermal stability of bacterial cellulose aerogel fibers and flame-retardant fire warning bacterial cellulose aerogel fibers; the heating rate is set to 10°C / min, the test temperature range is 30-900°C, the gas atmosphere is nitrogen, and the gas flow rate is 50mL / min.

[0085] In the present invention, a DMM5100 resistance meter is used to measure the response performance of the flame-retardant fire warning bacterial cellulose aerogel fiber to flame; the flame source is an alcohol lamp, and the aerogel fiber is woven into a 2cm×2cm fabric for testing.

[0086] In the present invention, an infrared thermal imager is used to measure the heat insulation performance of the flame-retardant fire warning bacterial cellulose aerogel fiber.

[0087] Example 1

[0088] Preparation of flame retardant fire warning bacterial cellulose aerogel fibers:

[0089] (1) Preparation of bacterial cellulose hydrogel fiber: Weigh 1 g of bacterial cellulose powder and dissolve it in 19 g of 7% LiCl solution (solvent is N,N-dimethylacetamide), and stir it ultrasonically for 5 h to prepare bacterial cellulose spinning solution; place the spinning solution in a wet spinning device for spinning, the inner diameter of the spinning needle is 0.7 mm, the extrusion rate is 80 μL / min, and after 1.2 times drawing in a deionized water coagulation bath, bacterial cellulose hydrogel fiber is obtained;

[0090] (2) Preparation of PA@PPy flame retardant conductive layer: Weigh 2.468 g (0.036 mol) of pyrrole, 4.052 g (0.006 mol) of phytic acid, and 20 g of isopropanol to obtain a mixed solution, and place the bacterial cellulose hydrogel fiber obtained in step (1) into the mixed solution and let it stand for 5 min; weigh 3.68 g of ammonium persulfate and dissolve it in 20 mL of water to obtain an ammonium persulfate solution, and then quickly add the ammonium persulfate solution to the mixed solution, and let it stand for 5 min. Finally, take out the soaked bacterial cellulose hydrogel fiber and wash it with deionized water for 2 to 3 times to remove excess polypyrrole on the surface to obtain a conductive cellulose hydrogel fiber;

[0091] (3) Preparation of ZnO@MXene nanohybrid materials: 2 g of lithium fluoride was added to 40 mL of 9 M hydrochloric acid aqueous solution, reacted at 25 °C for 30 min, and then the temperature was raised to 35 °C. Then 2 g of Ti was added. 3 AlC 2 The reaction was continued for 24 hours, and then the reaction solution was centrifuged, the lower precipitate was retained and washed with water until its pH was 7±0.5, and then the washed precipitate was mixed with water and ultrasonicated for 60 minutes, and the upper suspension was collected and freeze-dried to obtain 2D Ti 3 C 2 T x Monolayer nanosheets (MXene powder); 1.04 g zinc nitrate hexahydrate, 1.6 g sodium hydroxide, and 0.665 g MXene powder were weighed and added into 50 mL deionized water, and after ultrasonic stirring for 30 min, they were transferred into a hydrothermal reactor and subjected to hydrothermal reaction at 120 ° C for 12 h. Finally, the reaction product was washed and dried to obtain ZnO@MXene nanohybrid material;

[0092] (4) Preparation of fire warning layer: The ZnO@MXene nanohybrid material obtained in step (3) was added to water and ultrasonically stirred for 1 h to prepare a dispersion with a concentration of 5 mg / mL. The conductive cellulose hydrogel fiber obtained in step (2) was immersed in the above dispersion for 20 min, and then the immersed conductive cellulose hydrogel fiber was taken out and freeze-dried (freeze-drying temperature was -40°C and time was 48 h) to obtain flame-retardant fire warning bacterial cellulose aerogel fiber.

[0093] The preparation flow chart of flame retardant fire warning bacterial cellulose aerogel fiber is as follows Figure 1 shown.

[0094] The digital photo of the flame retardant fire warning bacterial cellulose aerogel fiber prepared in Example 1 is as follows: Figure 2 shown.

[0095] The digital photo of the flame retardant fire warning bacterial cellulose aerogel fiber fabric prepared in Example 1 exposed to the flame of an alcohol lamp is shown in FIG. Figure 3 shown.

[0096] The flame retardant fire warning bacterial cellulose aerogel fiber prepared in Example 1 was tested by Fourier infrared spectroscopy. The results are as follows: Figure 4 As shown. It can be observed that: 3445cm -1 The characteristic NH peak at 3334 cm -1 The hydroxyl absorption peak at 1557 cm -1 The absorption peak of CN bond is at 1255 -1 cm -1 The absorption peak at 1034cm is the characteristic peak of PO. -1 The peak at the center is the stretching vibration absorption peak of COC, which is consistent with the expected structural characteristics, proving that the target product was successfully prepared.

[0097] The flame retardant fire warning bacterial cellulose aerogel fiber and bacterial cellulose hydrogel fiber prepared in Example 1 were subjected to scanning electron microscopy, thermal stability, heat release rate (HRR), total heat release (THR), fire warning, and thermal insulation performance tests, and the results were as follows: Figures 5 to 10 The specific performance results are shown in Table 1.

[0098] Table 1 Flame retardant fire warning bacterial cellulose aerogel fiber performance data

[0099]

[0100] Compared with the unmodified bacterial cellulose aerogel fiber, the peak heat release rate of the flame-retardant fire warning bacterial cellulose aerogel fiber prepared in Example 1 is reduced by 80.6%, the total heat release is reduced by 88.4%, and the flame retardant performance is significantly improved; the residual carbon amount at 800°C is 19.5% higher, indicating that the flame-retardant fire warning bacterial cellulose aerogel fiber prepared in Example 1 has more superior thermal stability; the flame response sensitivity and flame response intensity data show that Example 1 has excellent fire warning function and expands the application range of bacterial cellulose fibers; in addition, the temperature difference under 90°C background is slightly higher than that of pure bacterial cellulose aerogel fiber, reaching 45.1°C, showing excellent thermal insulation performance.

[0101] The preparation method of the present invention is simple and controllable, the adopted aerogel fiber matrix is ​​green and environmentally friendly, and the prepared flame-retardant fire warning aerogel fiber exhibits excellent flame-retardant effect and high-efficiency flame sensitivity.

[0102] Example 2

[0103] This embodiment uses different amounts of phytic acid added to prepare flame-retardant fire warning bacterial cellulose aerogel fibers.

[0104] Single factor control: Referring to the steps of Example 1, only the addition amount of phytic acid in step (2) was replaced by 0.006 mol with 0.002 mol, 0.004 mol, 0.008 mol and 0.01 mol respectively, and other conditions remained unchanged, to prepare a series of flame retardant fire warning bacterial cellulose aerogel fibers.

[0105] The properties of the flame retardant fire warning bacterial cellulose aerogel fibers were measured, and the results are shown in Table 2.

[0106] Table 2 Performance data of flame-retardant fire warning bacterial cellulose aerogel fibers prepared with different phytic acid addition amounts

[0107]

[0108]

[0109] It can be seen that when other conditions remain unchanged, the flame retardant effect is improved with the increase of phytic acid addition, the flame sensitivity does not change much, and the thermal insulation performance decreases. However, when the phytic acid addition amount increases to 0.008 mol, the thermal insulation performance is greatly reduced. This is because the addition of excessive phytic acid destroys the skeleton structure inside the bacterial cellulose aerogel fiber, causing the internal structure to collapse. This defect will significantly reduce the application of the bacterial cellulose aerogel fiber in the direction of high-efficiency thermal insulation flame retardant fire warning textiles. Therefore, the optimal amount of phytic acid addition is 0.006 mol.

[0110] Example 3

[0111] This embodiment uses different zinc sources to prepare flame-retardant fire warning bacterial cellulose aerogel fibers.

[0112] Single factor control: Referring to the steps of Example 1, only the zinc source in the hydrothermal reaction of step (3) was replaced from zinc nitrate hexahydrate to equimolar amounts of zinc chloride (0.46 g) and zinc acetate (0.62 g), and other conditions remained unchanged to prepare a series of flame-retardant fire warning bacterial cellulose aerogel fibers.

[0113] The properties of the flame retardant fire warning bacterial cellulose aerogel fibers were measured, and the results are shown in Table 3.

[0114] Table 3 Performance data of flame-retardant fire warning bacterial cellulose aerogel fibers prepared with different zinc sources

[0115]

[0116] It can be seen that when other conditions remain unchanged, the performance of the flame retardant fire warning bacterial cellulose aerogel fiber does not change significantly after the zinc source in the hydrothermal reaction is replaced from zinc nitrate hexahydrate to zinc chloride and zinc acetate respectively.

[0117] Example 4

[0118] This example uses different ZnO@MXene dispersion concentrations to prepare flame-retardant fire warning bacterial cellulose aerogel fibers.

[0119] Single factor control: Referring to Example 1, only the concentration of ZnO@MXene dispersion in step (4) was replaced from 5 mg / mL to 1 mg / mL, 3 mg / mL, 7 mg / mL and 9 mg / mL respectively, and other conditions remained unchanged, to prepare a series of flame-retardant fire warning bacterial cellulose aerogel fibers.

[0120] The properties of the flame retardant fire warning bacterial cellulose aerogel fibers were measured, and the results are shown in Table 4.

[0121] Table 4 Performance data of flame retardant fire warning bacterial cellulose aerogel fibers at different ZnO@MXene dispersion concentrations

[0122]

[0123] It can be seen that when other conditions remain unchanged, the concentration of ZnO@MXene dispersion increases, the flame retardant performance, thermal stability, flame sensitivity and flame response intensity of flame retardant fire warning bacterial cellulose aerogel fiber increase, and when the concentration is higher than 5 mg / mL, the increase in flame response intensity decreases significantly and is close to saturation, and the thermal insulation performance also decreases significantly. Therefore, the concentration of ZnO@MXene dispersion is preferably about 5 mg / mL.

[0124] Example 5

[0125] This embodiment uses different sensing nanomaterials @MXene nanocomposites to prepare flame-retardant fire warning bacterial cellulose aerogel fibers.

[0126] Single factor control: Referring to Example 1, only the ZnO generated on the MXene surface by the hydrothermal reaction in step (3) was replaced by CuO and SnO 2 , other conditions remain unchanged, and flame retardant fire warning bacterial cellulose aerogel fibers are prepared. The specific operation is:

[0127] Preparation of CuO@MXene nanohybrid material: 2 g of lithium fluoride was added to 40 mL of 9 M hydrochloric acid solution, reacted at room temperature for 30 min, then the temperature was raised to 35 °C, and 2 g of Ti 3 AlC 2 , react for 24 hours, centrifuge, remove the lower precipitate, wash with water to pH = 7 ± 0.5, ultrasonicate for 60 minutes, collect the upper suspension, freeze-dry, and obtain 2D Ti 3 C 2 T x Monolayer nanosheets (MXene powder). 31.7 mg copper acetate, 120 mg sodium hydroxide, 21.6 mg Ti 3 C 2 T x The monolayer nanosheets were mixed with 30 mL of water and magnetically stirred for 30 min, then transferred into a hydrothermal reactor for hydrothermal reaction at 140 °C for 24 h. After cooling to room temperature, the nanosheets were taken out, washed with water, and vacuum dried to obtain CuO@MXene nanohybrid materials.

[0128] SnO 2 Preparation of MXene nanohybrid materials: 2 g of lithium fluoride was added to 40 mL of 9 M hydrochloric acid solution. After reacting at room temperature for 30 min, the temperature was raised to 35 °C and 2 g of Ti was added. 3 AlC 2 , react for 24 hours, centrifuge, remove the lower precipitate, wash with water to pH = 7 ± 0.5, ultrasonicate for 60 minutes, collect the upper suspension, freeze-dry, and obtain 2D Ti 3 C 2 T x Monolayer nanosheets (MXene powder). 90 mg of stannous chloride dihydrate, 294 mg of sodium hydroxide, 105 mg of Ti 3 C 2 T x The single-layer nanosheet was mixed with 30 mL of water and magnetically stirred for 30 min, then transferred into a hydrothermal reactor for hydrothermal reaction at 180 °C for 12 h, cooled to room temperature, taken out, washed with water, and vacuum dried to obtain SnO 2 @MXene nanohybrid materials.

[0129] MoS 2 Preparation of MXene nanohybrid materials: 2 g of lithium fluoride was added to 40 mL of 9 M hydrochloric acid solution. After reacting at room temperature for 30 min, the temperature was raised to 35 °C and 2 g of Ti was added. 3 AlC 2 , react for 24 hours, centrifuge, remove the lower precipitate, wash with water to pH = 7 ± 0.5, ultrasonicate for 60 minutes, collect the upper suspension, freeze-dry, and obtain 2D Ti 3 C 2 T xMonolayer nanosheets (MXene powder). 150 mg of sodium molybdate dihydrate, 112.5 mg of thiourea, and 120 mg of Ti3C2Tx monolayer nanosheets were mixed with 50 mL of water and magnetically stirred for 30 min. The system pH was adjusted to 3 with hydrochloric acid and then transferred to a hydrothermal reactor for hydrothermal reaction at 210 °C for 24 h. After cooling to room temperature, the monolayer nanosheets were taken out, washed with water, and vacuum dried to obtain MoS 2 @MXene nanohybrid materials.

[0130] The properties of the flame retardant fire warning bacterial cellulose aerogel fibers were measured, and the results are shown in Table 5.

[0131] Table 5 Performance data of flame-retardant fire warning bacterial cellulose aerogel fibers prepared by different sensing nanomaterials

[0132]

[0133] It can be seen that when other conditions remain unchanged, the ZnO generated by the hydrothermal reaction on the MXene surface is replaced by CuO and SnO 2 After that, the flame sensitivity and flame response intensity of the flame retardant fire warning bacterial cellulose aerogel fiber were reduced. 2 After that, the flame retardant performance is improved, but the flame sensitivity and flame response intensity are reduced. Therefore, the effect of ZnO in flame retardant fire warning bacterial cellulose aerogel fiber is the best.

[0134] Example 6

[0135] This embodiment uses different two-dimensional materials to prepare flame-retardant fire warning bacterial cellulose aerogel fibers.

[0136] Single factor control: Referring to Example 1, only the two-dimensional material participating in the hydrothermal reaction in step (3) was replaced by graphene oxide and boron nitride of equal mass from MXene, and other conditions remained unchanged, to prepare flame-retardant fire warning bacterial cellulose aerogel fibers.

[0137] The properties of the flame retardant fire warning bacterial cellulose aerogel fibers were measured, and the results are shown in Table 6.

[0138] Table 6 Performance data of flame-retardant fire warning bacterial cellulose aerogel fibers prepared by different sensing nanomaterials

[0139]

[0140] It can be seen that when other conditions remain unchanged, the flame sensitivity and flame response intensity of the flame retardant fire warning bacterial cellulose aerogel fiber are reduced after the two-dimensional material participating in the hydrothermal reaction is replaced by graphene oxide and boron nitride from MXene. Therefore, MXene is the best two-dimensional material for flame retardant fire warning bacterial cellulose aerogel fiber.

[0141] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing flame-retardant fire warning bacterial cellulose aerogel fiber, characterized in that: The preparation method comprises the following steps: (1) Preparation of bacterial cellulose hydrogel fibers: placing bacterial cellulose powder in an organic solvent and stirring to prepare a spinning solution, and wet spinning the spinning solution to obtain bacterial cellulose hydrogel fibers; (2) Preparation of PA@PPy flame retardant conductive layer: phytic acid, pyrrole and low molecular weight alcohol are mixed to prepare a mixed solution, and the cellulose hydrogel fiber prepared in step (1) is immersed in the mixed solution, and then an ammonium persulfate solution is added. After standing, the cellulose hydrogel fiber is taken out and washed to obtain a conductive cellulose hydrogel fiber; the concentration of phytic acid in the mixed solution is 0.2-0.3 g / mL, and the concentration of pyrrole is 0.1-0.2 g / mL; (3) Preparation of fire warning layer: adding ZnO@MXene nano-hybrid material into water and stirring to form a dispersion, immersing the conductive cellulose hydrogel fiber obtained in step (2) into the dispersion, and then taking out the conductive cellulose hydrogel fiber and freeze-drying it to obtain flame-retardant fire warning bacterial cellulose aerogel fiber; The preparation method of the ZnO@MXene nano-hybrid material is as follows: lithium fluoride is added to a hydrochloric acid aqueous solution for reaction, and then Ti3AlC2 is added to continue the reaction, and then the reaction solution is centrifuged, the precipitate is retained and washed with water until its pH is neutral, and then the washed precipitate is mixed with water and ultrasonicated, and the upper suspension is collected and freeze-dried to obtain MXene powder; zinc source, sodium hydroxide, and MXene powder are weighed and added to water, and a hydrothermal reaction is carried out after stirring, and then the obtained reaction product is washed with water and dried to obtain the ZnO@MXene nano-hybrid material.

2. The preparation method according to claim 1, characterized in that: In step (1), the organic solvent includes one or more of N,N-dimethylacetamide, N-methylpyrrolidone, acetone, dimethyl sulfoxide, toluene, tetrahydrofuran, acetonitrile, cyclohexanone, cyclohexane, and ethyl acetate; and the concentration of bacterial cellulose in the spinning solution is 5 to 15 wt%.

3. The preparation method according to claim 1, characterized in that In step (1), the wet spinning is performed by using a wet spinning device, the inner diameter of the spinning needle is 0.5 to 1 mm, and the extrusion rate is 50 to 100 μL / min.

4. The preparation method according to claim 1, characterized in that: In step (2), the concentration of phytic acid in the mixed solution is 0.25-0.28 g / mL.

5. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the ammonium persulfate solution is 0.1-0.2 g / mL; and the mass ratio of the phytic acid to the ammonium persulfate is 1-1.5:

1.

6. The preparation method according to claim 1, characterized in that: In the preparation method of ZnO@MXene nanohybrid material, the concentration of the hydrochloric acid aqueous solution is 5-10M, the ratio of the mass of lithium fluoride to the volume of the hydrochloric acid aqueous solution is 1g:10-30mL, and the mass ratio of lithium fluoride to Ti3AlC2 is 1-1.5:

1.

7. The preparation method according to claim 1, characterized in that: In the preparation method of ZnO@MXene nano-hybrid material, the mass ratio of zinc source to sodium hydroxide is 1-3:3-8, the mass ratio of zinc source to MXene powder is 1-3:1-5, the temperature of hydrothermal reaction is 120-170°C, and the time is 10-20h.

8. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the ZnO@MXene nano-hybrid material in the dispersion is 3 to 10 mg / mL; the immersion time is 10 min to 60 min, and the immersion temperature is 15 to 30°C.

9. A flame retardant fire warning bacterial cellulose aerogel fiber, characterized in that: The flame retardant fire warning bacterial cellulose aerogel fiber is composed of: a fiber layer, a phytic acid-doped polypyrrole flame retardant conductive layer and a ZnO@MXene nano-hybrid material flame sensing layer from the inside to the outside; The fiber layer is prepared by wet spinning of a spinning solution prepared from bacterial cellulose powder; The phytic acid-doped polypyrrole flame-retardant conductive layer is constructed on the surface of cellulose hydrogel fiber by in-situ chemical oxidation polymerization, using phytic acid as a dopant, pyrrole as a monomer, ammonium persulfate as an initiator, and low molecular weight alcohols as a displacement solvent. The fire warning layer is composed of ZnO@MXene nano-hybrid material; the preparation method of ZnO@MXene nano-hybrid material is as follows: lithium fluoride is added to a hydrochloric acid aqueous solution for reaction, and then Ti3AlC2 is added to continue the reaction, and then the reaction solution is centrifuged, the precipitate is retained and washed with water until its pH is neutral, and then the washed precipitate is mixed with water and ultrasonically treated, the upper suspension is collected and freeze-dried to obtain MXene powder; zinc source, sodium hydroxide, and MXene powder are weighed and added to water, and a hydrothermal reaction is carried out after stirring, and then the obtained reaction product is washed with water and dried to obtain ZnO@MXene nano-hybrid material.

10. Use of the flame-retardant fire warning bacterial cellulose aerogel fiber obtained by the preparation method according to any one of claims 1 to 8 or the flame-retardant fire warning bacterial cellulose aerogel fiber according to claim 9 in the fields of textiles, clothing, furniture or decorations.

Citation Information

Patent Citations

  • Conductive composite material with high flame retardancy and preparation method thereof

    CN111718517A

  • Flame-retardant Chinese art paper with fire early warning function and preparation method of flame-retardant Chinese art paper

    CN115948938A

  • Preparation method of BC-derived carbon-based nanofiber electrode material, electrode material and application

    CN117747780A

  • MoS < 2 >-MXene-based gas-sensitive flame-retardant coating and application thereof to textiles

    CN118390291A

Cited By

  • Carboxylated cellulose nanofiber aerogel and application thereof

    CN120682540A

  • Preparation of isotropic flame-retardant bacterial cellulose aerogel and application of isotropic flame-retardant bacterial cellulose aerogel in fire early warning

    CN120966084A